How The International Norms Travel: Disaster Risk Reduction Norms in the Aceh Post Disaster Rehabilitation and Reconstruction Program 2004 - Herningtyas, Ratih (Technium Social Sciences Journal, 2023)
The purpose of this study is to investigate the logic of the Indonesian government in carrying out the rehabilitation and reconstruction program following the December 26, 2004 earthquake and tsunami disaster in Aceh. This calamity has resulted in several casualties, property loss, and extensive damage to infrastructure and dwellings. After the emergency response process, one of the key goals for restoring people’s life is to implement the rehabilitation and reconstruction program. Using Finnemore and Sikkink’s norms life cycle, this article demonstrates that the rehabilitation and reconstruction program represents not only the interests and obligations of the Indonesian government in general, but also the influence of international norms that mandate state policies and acts. This article discovered that disaster risk reduction, as symbolized by the motto Build Back Better, is an international norm that affected the Indonesian government’s implementation of the rehabilitation and reconstruction program in Aceh. It may be traced back to the process of its emergence, socialization in international forums, and internalization in the planning and implementation of the Aceh government’s rehabilitation and reconstruction program.